Multitasking muscle: engineering iPSC-derived myogenic progenitors to do more - Hamer, Mark Stephen; Rossi, Fabio M. V. (Frontiers in Cell and Developmental Biology, 2025)
The generation of myogenic progenitors from iPSCs (iMPs) with therapeutic potential for in vivo tissue regeneration has long been a goal in the skeletal muscle community. Today, protocols enable the production of potent, albeit immature, iMPs that resemble Pax7+ adult muscle stem cells. While muscular dystrophies are often the primary therapeutic target for these cells, an underexplored application is their use in treating traumatic muscle injuries. Notably absent from recent reviews on iMPs is the concept of engineering these cells to perform functions post-transplantation that non-transgenic cells cannot. Here, we highlight protocols to enhance the generation, purification, and maturation of iMPs, and introduce the idea of engineering these cells to perform functions beyond their normal capacities, envisioning novel therapeutic applications.